DEVELOPING CROSS-CULTURAL UNDERSTANDING (CCU) MATERIALS IN TOURISM GUIDING FOR VOCATIONAL STUDENTS - Anis Nurul Hidayah Nafa; Miftha Yuliana; Nana Parama Sari; Wuri Anggraini; Fardini Sabilah; Mohammad Kholilurrahman Jailani (English Review: Journal of English Education, 2023)
Learning English for Specific Purpose (ESP) for vocational students, is very important so that certain ways are needed to encourage students' needs. Students must receive sufficient material in certain ways based on their interests and majors. This study aims to analyze learning needs of tourism guide materials. The method used in this study is qualitative and quantitative research design where the data is collected with numerical form then described in the form of a description. The research instruments used in this study are questionnaires and open-ended interviews. This study conducts a needs analysis to measure student needs and to develop ESP materials. The participants of this research are 3rd and 4th semester students majoring in D3 Vocational Department UNMER Malang. The results of the study indicate the needs of students to improve their English-speaking skills and develop Cross Cultural Understanding (CCU) as tourism guiding materials. Furthermore, students' English skills also show low results which lead to low self-confidence because the learning methods used by lecturers have not developed due to the application of teacher-centered classes which lead to a lack of practice from students. Therefore, learning methods that are able to stimulate students’ speaking proficiency and CCU material development are needed.